Smoking Cessation and Preterm Birth in Second Pregnancy Among Women who Smoked in Their First - Pereira, Gavin; Dunne, Jennifer; Regan, Annette; Tessema, Gizachew (Oxford University Press, 2021)
Introduction: The benefit of smoking cessation in reducing the risk of preterm birth is well established. Relatively less well understood is the prevalence of smoking cessation maintenance at the next pregnancy and the associated preterm risk reduction. The aim of this study was to estimate the prevalence of maintenance of smoking cessation at second pregnancy and the associated relative risk of preterm birth. Methods: This was a longitudinal study with retrospectively obtained records of births to multiparous women who smoked in the pregnancy of their first birth in New South Wales, 1994–2016 (N = 63 195 mothers). Relative risks (RR) of preterm birth of the second child were estimated for smoking cessation with adjustment for final gestational age of the first birth, maternal age at the first birth, change in socioeconomic disadvantage between the first and second pregnancy, interpregnancy interval, and calendar time. Results: Approximately 34% (N = 21 540) of women who smoked during their first pregnancy did not smoke in the second pregnancy. Smoking cessation among women who smoked at first pregnancy was associated with a 26% (95% CI: 21%, 31%) decrease in risk of preterm birth at a second pregnancy. Conclusion: Despite smoking during the first pregnancy, smoking cessation was achieved and maintained by more than one-third of women in their second pregnancy with encouraging levels of preterm risk reduction. It is well-established that the period after birth provides an opportunity to reduce smoking-related morbidity for both the mother and neonate. Our results indicate that this period also offers an opportunity to prevent morbidity of future pregnancy. Implications: A considerable amount of research has been undertaken on the effects of smoking during pregnancy on birth outcomes, the influence of postpartum smoking on the health of the mother and newborn child, and postpartum smoking cessation. However, follow-up of women after giving birth does not tend to be long enough to observe smoking and outcomes of subsequent pregnancies. We show that smoking cessation in the subsequent pregnancy is achievable by a large proportion of women despite smoking in their first pregnancy, which translates to clear reductions in risk of preterm birth in the subsequent pregnancy.